Sound Changes of Batu Bara Malay Dialect from Proto Austronesian Language - Rini Rezeki; Dwi Widayati (Tradition and Modernity of Humanity, 2024)
This research aims to analyze the sound changes and how it changes in the Proto-Austronesian language to Batu Bara Dialect Malay. The research method uses quantitative methods. Data collection and collection were obtained in the field using the method of chapping, and recording. The location and time of the research were conducted in the Kampung Lalang Village area, Tanjung Tiram District, Batu-Bara Regency, North Sumatra Province. The data source consists of a list of 200 basic swadesh and PAN vocabulary from the book An Introduction Historical Linguistics Fourth Edition by Crowley and Bowern. Then the data will be analyzed in the form of procedures. Grouping between glosses (200 basic vocabulary), PAN Language, and Batu Bara Dialect Malay Language (MBB). b. Grouping data according to sound changes, c. Analyzing changes in sound changes from both languages between PAN and MBB. The results of the analysis that has been done about the sound changes from PAN to MBB can be concluded that sound changes based on place are found in metathesis, aphaeresis, syncope, apocope, prosthesis, assimilation, paragoge, inheritance of innovation, epenthesis, lenition.